2
$\begingroup$

I'm having some trouble proving that the Taylor series about the origin of the function $[Log(1-z)]^2$ to be $$\sum_{n=1}^\infty \frac{2H_n}{n+1}z^{n+1}$$ where $$H_n = \sum_{j=1}^n \frac{1}{j}$$

So far, I've been trying to use the definition of Log(1-z) = log|1-z| + iArg(1-z). I've also noted that the Taylor expansion for log|1-z| = $\sum_{k=0}^\infty \frac{-z^{k+1}}{k+1}$ from integrating the geometric series $\sum_{k=0}^\infty z^k$ given |z|<1.

Because log|1-z| = $\sum_{k=0}^\infty \frac{-z^{k+1}}{k+1}$ converges for |z|<1, I've tried to use this for the Cauchy product of [Log(1-z)]^2

$$[Log(1-z)]^2 = Log(1-z) Log(1-z)$$ $$=\left(\sum_{i=0}^\infty \frac{-z^{i+1}}{i+1}\right)\left(\sum_{j=0}^\infty \frac{-z^{j+1}}{j+1}\right)$$ $$=\sum_{n=0}^\infty \sum_{k=0}^n\frac{-z^{k+1}}{k+1} \frac{-z^{n-k+1}}{n-k+1}$$ $$= \sum_{n=0}^\infty \sum_{k=0}^n\frac{z^{n+2}}{(k+1)(n-k+1)}$$

Really lost here, so any clues would be helpful! Thank you in advance.

$\endgroup$
1
$\begingroup$

The next step might be to use partial fractions:

$\dfrac1{k+1}+\dfrac1{n-k+1} =\dfrac{(n-k+1)+(k+1)}{(k+1)(n-k+1)} =\dfrac{n+2}{(k+1)(n-k+1)} $ so $\dfrac{1}{(k+1)(n-k+1)} =\dfrac1{n+2}\left(\dfrac1{k+1}+\dfrac1{n-k+1}\right) $.

Therefore

$\begin{array}\\ \sum \limits_{n=0}^\infty \sum \limits_{k=0}^n\dfrac{z^{n+2}}{(k+1)(n-k+1)} &=\sum \limits_{n=0}^\infty \sum \limits_{k=0}^nz^{n+2}\dfrac1{n+2}\left(\dfrac1{k+1}+\dfrac1{n-k+1}\right)\\ &=\sum \limits_{n=0}^\infty \dfrac{z^{n+2}}{n+2}\sum \limits_{k=0}^n\left(\dfrac1{k+1}+\dfrac1{n-k+1}\right)\\ &=\sum \limits_{n=0}^\infty \dfrac{z^{n+2}}{n+2}\left(\sum \limits_{k=1}^{n+1}\dfrac1{k}+\sum \limits_{k=0}^{n}\dfrac1{n-k+1}\right)\\ &=\sum \limits_{n=0}^\infty \dfrac{z^{n+2}}{n+2}\left(H_{n+1}+\sum \limits_{k=1}^{n+1}\dfrac1{k}\right)\\ &=\sum \limits_{n=0}^\infty \dfrac{z^{n+2}}{n+2}2H_{n+1}\\ &=\sum \limits_{n=1}^\infty \dfrac{z^{n+1}}{n+1}2H_{n}\\ \end{array} $

$\endgroup$
2
$\begingroup$

Outline: I would attack the problem somewhat differently. First multiply the power series for $\ln(1-t)$ by the series for $\frac{2}{1-t}$. The $2H_k$ will come up naturally as coefficients.

Then integrate term by term from $0$ to $z$. That will produce the right denominator.

Finally, calculate $\int_0^z\frac{2}{1-t}\ln(1-t)\,dt$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.